2001
DOI: 10.1038/labinvest.3780323
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Phosphodiesterase Isoforms III or IV Suppress Islet-Cell Nitric Oxide Production

Abstract: SUMMARY:The general phosphodiesterase (PDE) inhibitor pentoxifylline (PTX), and the PDE type IV inhibitor rolipram (ROL), both increase intracellular cAMP levels and suppress inflammatory cytokine production by T cells and macrophages. We have previously shown that PTX and ROL protect from autoimmune diabetes in nonobese diabetic (NOD) mice. These drugs may mediate some of their anti-inflammatory effects by blocking nitric oxide (NO) production by macrophages. In this study, we investigated the effect of PDE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Although rofl umilast has benefi cial biological effects, its mechanism in infl ammatory cells has not yet been clearly demonstrated. It was recently reported that rolipram, a PDE4 specifi c inhibitor, and pentoxifylline, a general PDE inhibitor, suppressed NO production in islet cells [27] and macrophages [28].…”
Section: Introductionmentioning
confidence: 99%
“…Although rofl umilast has benefi cial biological effects, its mechanism in infl ammatory cells has not yet been clearly demonstrated. It was recently reported that rolipram, a PDE4 specifi c inhibitor, and pentoxifylline, a general PDE inhibitor, suppressed NO production in islet cells [27] and macrophages [28].…”
Section: Introductionmentioning
confidence: 99%
“…While this effect can be explained by inhibition of cytokine production by pro-inflammatory cells such as macrophages there could also be a contribution from an inhibition of nitric oxide production by islet cells in response to cytokines. Thus pentoxifylline and the selective PDE3 inhibitor cilostamide blocked nitric oxide production by mouse islet cells and a beta-cell line (NIT-1) in response to stimulation by lipopolysaccharide and inflammatory cytokines [96] and prevented the expression of inducible nitric oxide synthase both in vitro and in vivo in the NOD mouse. This supports earlier findings that IBMX reduced IL-1β induced nitric oxide synthase expression and nitric oxide production in rat islets, an effect mimicked by dibutyryl cyclic AMP [41].…”
Section: Pdes In Other Islet Cell Typesmentioning
confidence: 99%
“…While this effect may be explained by inhibition of cytokine production by pro-inflammatory cells such as macrophages, there may also be a contribution from an inhibition of nitric oxide production by islet cells in response to cytokines. Thus pentoxifylline and the selective PDE3 inhibitor cilostamide blocked nitric oxide production by mouse islet cells and a -cell line (NIT-1) in response to stimulation by lipopolysaccharide and inflammatory cytokines (Besay & Prud'homme 2001) and prevented the expression of inducible nitric oxide synthase both in-vitro and invivo in the NOD mouse. This supports earlier findings that IBMX reduced interleukin-1-induced nitric oxide synthase expression and nitric oxide production in rat islets, an effect mimicked by dibutyryl cAMP (Andersen et al 1996).…”
Section: Pde Inhibitorsmentioning
confidence: 99%